2021
DOI: 10.1029/2020pa004091
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Ancient DNA From the Subarctic North Pacific: How Sea Ice, Salinity, and Insolation Dynamics Have Shaped Diatom Composition and Richness Over the Past 20,000 Years

Abstract: Climate warming is transforming arctic and subarctic ecosystems by a reduction in the duration, extent, and thickness of sea ice (Parkinson et al., 1999;Walsh et al., 2017)-a key variable of the global climate system whose disappearance is resulting in a positive temperature feedback from a reduction of the surface albedo (Pistone et al., 2014). Rapidly melting glaciers and increased riverine runoff resulting from thawing permafrost and augmented precipitation over the adjacent continents are expected to decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 85 publications
(135 reference statements)
0
19
0
Order By: Relevance
“…The similarity in the categorization of the sediments strongly suggests that the mineral and organic evolution occurred conjointly as a result of ecosystem development that had occurred in the late glaciation, deglaciation, and post-glaciation periods. Indeed, natural environmental changes that occurred during these periods can lead to such changes (e.g., Snowball et al 2002;Voldstad et al 2020;Zimmermann et al 2021).…”
Section: Tracking Sedimentary Characteristics Using a Combination Of Geochemical Techniques: Application In This Study And Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…The similarity in the categorization of the sediments strongly suggests that the mineral and organic evolution occurred conjointly as a result of ecosystem development that had occurred in the late glaciation, deglaciation, and post-glaciation periods. Indeed, natural environmental changes that occurred during these periods can lead to such changes (e.g., Snowball et al 2002;Voldstad et al 2020;Zimmermann et al 2021).…”
Section: Tracking Sedimentary Characteristics Using a Combination Of Geochemical Techniques: Application In This Study And Perspectivesmentioning
confidence: 99%
“…6d). This OM might have been preserved in ice-sheets, possibly in interglacial soils that deposited during deglaciation and post-glaciation, or might have come from organisms that formed during the Late Pleistocene (late glaciation or deglaciation periods) or Early Holocene (e.g., Zale et al 2018;Zimmermann et al 2021). Indeed, it was shown that vegetation was able to penetrate thin ice sheets during Late glaciation 14,000-11,000 years ago (Kullman 2002).…”
Section: First Sedimentary Materials Reaching the Lake After The Glacial Periodmentioning
confidence: 99%
See 3 more Smart Citations